Arsenic incorporation into FeS2 pyrite and its influence on dissolution: A DFT study - Blanchard, M.; Alfredsson, M.; Brodholt, J.; Wright, Kathleen; Catlow, R. (Pergamon, 2007)
FeS2 pyrite can incorporate large amounts of arsenic (up to ca. 10 wt%) and hence has a strong impact on the mobility of this toxic metalloid. Focussing on the lowest arsenic concentrations for which the incorporation occurs in solid solution, the substitution mechanisms involved have been investigated by assuming simple incorporation reactions in both oxidising and reducing conditions. The solution energies were calculated by Density Functional Theory (DFT) calculations and we predict that the formation of AsS dianion groups is the most energetically favourable mechanism. The results also suggest that the presence of arsenic will accelerate the dissolution and thus the generation of acid drainage, when the crystal dissolves in oxidising conditions.